2006
DOI: 10.1007/s11136-006-0028-6
|View full text |Cite
|
Sign up to set email alerts
|

Measuring meaning in life following cancer

Abstract: Meaning in life is a multi-faceted construct that has been conceptualized in diverse ways. It refers broadly to the value and purpose of life, important life goals, and for some, spirituality. We developed a measure of meaning in life derived from this conceptualization and designed to be a synthesis of relevant theoretical and empirical traditions. Two samples, all cancer patients, provided data for scale development and psychometric study. From exploratory and confirmatory factor analyses the Meaning in Life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 74 publications
7
68
0
7
Order By: Relevance
“…The group mean (44.3) was one half the standard deviation below the population mean of 50. Scores on the meaning subscales are comparable to those from cancer patients sampled for scale development [24]. Regarding depressive symptomatology, the mean score of the CES-D (4.30) was within the normal range, but inspection of individual scores showed that 21% of the sample had significant symptomatology.…”
Section: Analytic Strategymentioning
confidence: 70%
See 2 more Smart Citations
“…The group mean (44.3) was one half the standard deviation below the population mean of 50. Scores on the meaning subscales are comparable to those from cancer patients sampled for scale development [24]. Regarding depressive symptomatology, the mean score of the CES-D (4.30) was within the normal range, but inspection of individual scores showed that 21% of the sample had significant symptomatology.…”
Section: Analytic Strategymentioning
confidence: 70%
“…Meaning in Life-The Meaning in Life Scale is a 21-item measure (MLS; [24]), which conceptualizes meaning as a multidimensional construct present when one has a sense of purpose, coherence, and fulfillment in life and holds beliefs that life has value. Confirmatory factor analysis reveals that it is comprised of four dimensions: harmony and peace (four items; e.g., "I feel peaceful," "I can reach into myself for comfort"), life perspective, purpose, and goals (seven items; e.g., "I feel more fulfilled and satisfied with life," "I am settled about the future"), benefits of spirituality (three items: e.g., "I find comfort in my faith and spiritual beliefs," "I have strength in my spiritual beliefs"), and confusion and lessened meaning (seven items; "I get confused when I try to understand life," "Life has less meaning").…”
Section: Measures For Latent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some 20 scales were identified that measured meaning: the Chinese Cancer Coherence Scale (CCCS) (Chan et al, 2007); the Constructed Meaning Scale (Fife, 1995); the meaning/peace subscale of the Functional Assessment of Chronic Illness Therapy -Spiritual Well-Being Scale (FACIT-Sp) (Canada et al, 2008;Murphy et al, 2010;Peterman et al, 2002); the Illness Cognitions Questionnaire (ICQ) (Evers et al, 2001); the Internal Coherence Scale (ICS) (Kroz et al, 2009); the Life Attitude Profile (LAP)/ Life Attitude Profile -Revised (LAP -R) (Reker, 1992;Reker & Peacock, 1981); the Life Evaluation Questionnaire (LEQ) (Salmon et al, 1996); the Meaning in Life questions (including the Benefit Finding Scale [BFS]) used by Tomich and Helgeson (2002); the Meaning in Life Questionnaire (MLQ) (Steger et al, 2006); the Meaning in Life Scale (MILS) (Jim et al, 2006); the Meaning in Suffering Test (MIST) (Starck, 1983); the Perceived Meanings of Cancer Pain Inventory (PMCPI) (Chen, 1999); the Personal Meaning Profile (PMP) (Wong, 1998); the Positive Meaning and Vulnerability Scale (Bower et al, 2005); the Purpose in Life (PIL) Test (Crumbaugh & Maholick, 1964); the Purposelessness, Understimulation, and Boredom (PUB) Scale (Passik et al, 2003); the Schedule for Meaning in Life Evaluation (SMiLE) (Fegg et al, 2008); the Sense of Coherence (SOC) Scale (Antonovsky, 1993); the Sources of Meaning Profile (SOMP)/Sources of Meaning Profile -Revised (SOMP -R) (Reker, 1996); and the World Assumptions Scale (Janoff-Bulman, 1989). The optimal measure of meaning will vary depending on the purpose and context of the assessment.…”
Section: Meaningmentioning
confidence: 99%
“…As a social practice, a healthy life has its meanings, just as an unhealthy one does (2). Illness is a difficult problem which affects the normal cycle of life through negative experiences (3). Every illness has its specific experiences.…”
Section: Introductionmentioning
confidence: 99%